Critical Flow-Based Fast Algorithm for the Total Supply Capability Curve of Distribution Networks - Xiao, Jun; Qu, Yuqing; She, Buxin; Jiao, Heng; Li, Chengjin; Zhang, Shihao (Arabian journal for science and engineering (2011), 2023)
To alleviate the ‘curse of dimensionality’ and speed up the calculation of the total supply capability curve (TSC curve), this paper proposes a novel critical flow-based fast algorithm for distribution networks. Firstly, the critical flow and the TSC curve are found to have good correspondence through the comparison of their concepts and models. Secondly, a critical flow-based algorithm with three phases is proposed for calculating the TSC curve: (i). Determine the equivalent flow network of the distribution network; (ii). Solve critical flows of the equivalent flow network through a dimension reduction-sampling algorithm and obtain the corresponding TSC curve operating points; (iii). Calculate the flow value of the critical flow and plot the TSC curve. Finally, the proposed algorithm is verified by the expanded IEEE RBTS BUS4 case with soft open point (SOP). The application of the TSC curve in distribution network planning is demonstrated. In addition, the correctness and rapidity of the proposed algorithm are verified by comparing it with the existing sampling algorithm, and the reasons for the performance improvement are investigated. This paper applies the network flow theory to calculating the power supply capability of distribution networks for the first time, which simplifies the calculation of the TSC curve and increases the computational efficiency significantly.